Leader’s sensegiving and promotion of team sensemaking: Is one of these functions enough to increase team performance? - Passos, A. M.; Sinval, J.; Santos,C.M.; Sousa Guedes, A.; Uitdewilligen, S. (EURAM 2019 Conference, 2019)
Research has consistently showed the relevance of team leadership functions to promote team performance. This study investigates the influence of leader’s sensegiving on team performance as well as the moderator role of leader’s promotion of team sensemaking on the relationship between leader’s sensegiving and team performance. We tested our model with a sample of 82 teams (304 team members and 82 team leaders) from consultancy firms. Data was collected through two different survey questionnaires: one for team members and one for leaders. The results support our hypotheses revealing that the influence of leader’s sensegiving on team performance is higher in situations that leaders also promote sensemaking of team members. This study introduces a new leadership function, leader promotion of team sensemaking, and analyses its join influence with other relevant team leadership function on team performance. Leaders need to be trained in sensegiving behavior as well in promoting team sensemaking in order to guide their team towards effective processes and performance. Further research is suggested to extend the results of this relevant area of investigation.